2007
DOI: 10.1016/j.eururo.2006.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Synthase Keeps Erection Regulatory Function Balance in the Penis

Abstract: Objectives: We sought to evaluate the regulatory influence of endothelial nitric oxide (NO) on the basal functional states of the NO and RhoA/Rho-kinase signaling pathways in the penis employing endothelial NO synthase (eNOS) mutant mice and eNOS gene transfer technology.Methods: Four groups of mice were utilized: 1) wild type (WT), 2) eNOS gene deleted (eNOS −/−), 3) eNOS and neuronal NOS gene deleted (dNOS −/−), and 4) eNOS −/− mutant mice transfected intracavernosally with eNOS. Cyclic guanosine monophospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 33 publications
3
89
0
2
Order By: Relevance
“…Furthermore, reciprocal regulation of NOS by arginase has been demonstrated in cells and organs in which NO is an important signaling molecule, including the endothelium, cardiac myocytes, penis, airway, skin, and inflammatory cells [4][5][6]10,16,[29][30][31]. It was demonstrated that arginase II activity is upregulated in atherosclerosis-prone mice and is associated with impaired endothelial NO production, endothelial dysfunction, vascular stiffness, and ultimately, aortic plaque development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reciprocal regulation of NOS by arginase has been demonstrated in cells and organs in which NO is an important signaling molecule, including the endothelium, cardiac myocytes, penis, airway, skin, and inflammatory cells [4][5][6]10,16,[29][30][31]. It was demonstrated that arginase II activity is upregulated in atherosclerosis-prone mice and is associated with impaired endothelial NO production, endothelial dysfunction, vascular stiffness, and ultimately, aortic plaque development.…”
Section: Discussionmentioning
confidence: 99%
“…4) in which nNOS initiates the erectile response, which is then maintained and increased by eNOS activity (the latter being activated by shear stress) (Hurt et al, 2002(Hurt et al, , 2006Musicki and Burnett, 2006;Bivalacqua et al, 2007b;Musicki et al, 2009). eNOS has an indispensable role in the erectile response, and its activity and endothelial NO bioavailability are regulated by multiple post-translational molecular mechanisms, such as eNOS phosphorylation, eNOS interaction with regulatory proteins and contractile pathways, and actions of reactive oxygen species (ROS).…”
Section: J Nitric Oxide and Cgmp Signalingmentioning
confidence: 99%
“…Therefore, NO/cGMP/PKG-induced synapse remodeling is dependent on RhoA/ROCK signaling, involving phosphorylation of the ROCK substrate MLC before synapse withdrawal. Increased RhoA/ROCK activity resulting from long-term action of the NO/cGMP/PKG cascade has been previously suggested in arterial smooth muscle cells (Sauzeau et al, 2003), in the penis (Bivalacqua et al, 2007), and in hearts from diabetic rats (Soliman et al, 2008). In this sense, cGMP/PKG together with ROCK and/or MLC-kinase mediates growth cone collapse responses to ephrin-B1, -A5, and Semaphorin 3A in cells from different origins (Dontchev and Letourneau, 2002;Mann et al, 2003;Yue et al, 2008).…”
mentioning
confidence: 99%